Determinants of Pulmonary TB Incidence in Children Aged 0-14 Years in the Work Area of UPTD Puskesmas Sukorame - Lutfiati Anam, Indri; Ema Mayasari; Juvita Herdianty (Universitas STRADA Indonesia, 2025)
Tuberculosis is an infectious disease that can attack people of all ages caused by the bacteria Mycobacterium tuberculosis. Parental knowledge plays a role in parental behavior and awareness of disease prevention efforts. Exposure to cigarettes causes a decrease in the immune system, making it susceptible to disease. Nutritional status also plays a role in the body's immunity, where a body with good nutritional intake will strengthen the body's immunity so that it can attack incoming foreign antigens. BCG immunization is a basic immunization that must be given to children to help prevent tuberculosis. The purpose the research to find out the determinants of the incidence of pulmonary TB in children aged 0-14 years in the Sukorame Community Health Center UPTD Working Area. This research is a quantitative study using a cross sectional method. The research samples were positive TB sufferers and TB suspects who were recorded in children's TB reports in the Sukorame Community Health Center working area. The sampling technique uses purposive sampling. Data analysis used SPSS software with the chi square statistical test. Results: Based on the results of the chi square test, it was found that parents' knowledge about pulmonary TB had a p-value of 0.059 for children, family smoking habits had a p-value of 0.021 for children, children's nutritional status had a p-value of 1.000 for children, and children's BCG immunization status had a p-value of 0.577 for children's pulmonary TB. It can be concluded that the variable family smoking habits is related to the incidence of pulmonary TB in children, while the variables of knowledge, nutritional status and BCG immunization have no relationship.